The etiology of the emergence of COVID-19 in the framework of international transformation - Salloum, Feras Sadik (Journal of the Belarusian State University. International Relations, 2020)
With every event affecting humanity, there are conspiracy theories, messages and hypotheses promoted by politicians, the military, intellectuals and clerics in societies and countries. There are many hypotheses about the source of COVID-19. The aim of this article is to identify the alleged origin of this virus. The article examines the main sources of the emergence of COVID-19 and sheds light on the opposing opinions regarding the outbreak of the virus in question. A significant number of Arabic and English sources have been introduced into scientific circulation, which clarified the origins of this epidemic. Due to a number of reasons for the emergence of a pandemic, the authour will divide them into several groups, which will contain a certain hypothesis considered from different points of view.